Premchand: A Social Reformer And Creative Thinker - Surendra Kumar , Gupta (International Journal of Psychosocial Rehabilitation, 2017)
The objective of this research paper is to prominence the concealed reality of Indian social system and the suppression of low class people in India. The caste system has spread its roots deep in Indian society. The constitution of Indian society, with its hierarchy is an ideal place to better realize the practice of oppression. Lower class throughout the longest conventional Indian hierarchy and members of the lower castes and classes have usually born to force the repression generated by the Indian communal structure. Premchand is generally considers the greatest Hindi writer. Premchand was also a social reformer. The remarkable characteristic of his writing was the reality that he depicted as exploitation of poor people. He gave the massage on social evils like dowry, poverty, communalism and corruption. He was the first writer of twenty century to reflect reality in the literature. Premchand is the most prominent Hindi novelist, and Godaan is Premchand’s renowned novel. The economic and social struggle in a north village are deeply depicted the condition of the pre-independence of a countryside. That was the era of poverty, ignorance and exploitation of the illiterate peasants at the hands of rich landlords. But the situation has not changed as greatly as it had been expected and the subaltern condition cannot change completely life and survival of Hori’s family and self respect. Hori does everything to achieve his life to buy a cow. According to Hindu’s mythology of that time, he has a conviction that making the gift of a cow to a Brahman before he dies will help him attain salvation. An engaging introduction to India before Independent, Godaan is at once village ethnography, moving human document and perceptive of colonial history.